CF-Rice: Tool for calculating Carbon footprints of rice products - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The tool has been developed and tested. A manuscript has been submitted to a journal. User manual and Training materials have been prepared for launching and roll-out.